Windows NT Workstation 4.0 advanced technical reference - Boyce, Jim...[et al] (Que Corporation IndianapolisUS, 1996)
Covers a wide range of topics for configuring and using Windows NT's many advanced features on both Intel- and RISC-based systems. Focuses on implementation and covers key areas including: understanding Windows NT's architecture; components and new features; optimising network performance; managing the registry; and, administering workstation and user properties. Provides Windows NT glossary.